2015
DOI: 10.1007/s13726-015-0346-z
|View full text |Cite
|
Sign up to set email alerts
|

High-performance polyvinylidene fluoride/poly(styrene–butadiene–styrene)/functionalized MWCNTs-SCN-Ag nanocomposite membranes

Abstract: content on membrane performance and structure was studied using pertinent methods and techniques. Percentage of water content of PVDF/SBS-MWCNTs-SCN 0.01-0.1 was estimated around 1.08-2.80 % and this value was further increased to 1.94-4.65 % in silver nanoparticle-modified system. Moreover, the porosity of silver nanoparticle-modified system was found superior compared with the other composites. Pure water flux, salt rejection, and recovery were also found optimal for 0.05 wt% silver nanoparticlebased modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…from 83.3%, compared to when no Ag was used. These novel membranes showed potential for further improvement by using a combination of polymer-metal blends for advance water treatment which can be utilized prior to RO operations [226]. Hashaikeh et al [267] reported a fast and efficient in-situ cleaning method for CNT-based membranes through periodic electrolysis.…”
Section: Electrically Conductive Membranesmentioning
confidence: 99%
“…from 83.3%, compared to when no Ag was used. These novel membranes showed potential for further improvement by using a combination of polymer-metal blends for advance water treatment which can be utilized prior to RO operations [226]. Hashaikeh et al [267] reported a fast and efficient in-situ cleaning method for CNT-based membranes through periodic electrolysis.…”
Section: Electrically Conductive Membranesmentioning
confidence: 99%
“…Several techniques have been used to synthesize the MMCNT membranes (Figure 4). The widely employed methods by researchers include phase inversion [75][76][77][78], solution mixing [79,80], polymer grafting [81], in-situ polymerization [82][83][84] and in-situ colloidal precipitation [85], spray-assisted layer-by-layer [86] and interfacial polymerization [87].…”
Section: Types Of Nanotube Membranes and Their Fabricationmentioning
confidence: 99%
“…Solution blending has been used for synthesizing nanocomposite membranes of PVDF/poly(styrene-butadiene-styrene)/thiocyanate and silver-modified MWCNTs [80]. Liu et al [86] used the spray-assisted layer-by-layer technique to prepare the PES/functionalized MWCNT (F-MWCNTs) membrane.…”
Section: Types Of Nanotube Membranes and Their Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry weight (W dry ) was determined after 48 h drying at 75 °C. The WC ratio was calculated by the following equation [48,49]:…”
Section: Water Contentmentioning
confidence: 99%